2021
DOI: 10.1021/acs.energyfuels.1c02247
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Inhibition of CO2 Hydrate by Carboxymethylcellulose Sodium through Retarded Mass Transfer

Abstract: The influence of carboxymethylcellulose sodium (CMC-Na) on the formation kinetics of carbon dioxide (CO2) hydrate was investigated by adopting an isothermal and isochoric method. The mass transfer characteristics of CO2 in the solution of CMC-Na were also investigated. Pure water and polyvinylpyrrolidone (PVP) of different molecular weights were used for comparison. Several parameters, such as the concentration of the additives, the stirring condition, and the temperature, were investigated. The experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…In the kinetic reactor, a hydrate film was clearly observed in the pure water system, as shown in Figure (A7)­(image on theright). The formation of the hydrate films was also found in our previous work. , For the 1.0 wt % SDS solution, the hydrate started to nucleate at several points of the surface of the solution simultaneously. Then, a hydrate film also formed.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…In the kinetic reactor, a hydrate film was clearly observed in the pure water system, as shown in Figure (A7)­(image on theright). The formation of the hydrate films was also found in our previous work. , For the 1.0 wt % SDS solution, the hydrate started to nucleate at several points of the surface of the solution simultaneously. Then, a hydrate film also formed.…”
Section: Resultssupporting
confidence: 81%
“…However, when the concentration of l -Trp was 0.01 wt %, it had no promotion effects, as shown in Figure d. The formed hydrate film provides a mass-transfer barrier for the water molecules and the gas molecules to meet, and the amount of the formed hydrate was little . The l -Trp molecules could also change the property of the inner wall of the container and promote the upward climbing of the water molecules along it, as shown in Figure e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of PVP and L-tyrosine on the mixed gas hydrate's induction time was researched by Talaghat et al 33 The findings showed that L-tyrosine was more effective in inhibiting enzyme activity than PVP, and PVP performed better when L-tyrosine was added in modest amounts. The inhibitory impact of carboxymethylcellulose (CMC) on CO 2 hydrate was investigated by Shen et al 34 They believed that the inhibition mechanism of the CMC is mainly by mass transfer. CMC can slow down hydrate formation and reduce hydrate production, but there was no inhibitory effect when the concentration is less than 0.1 wt %.…”
Section: Introductionmentioning
confidence: 99%